23t-2=53t-92

Simple and best practice solution for 23t-2=53t-92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23t-2=53t-92 equation:


Simplifying
23t + -2 = 53t + -92

Reorder the terms:
-2 + 23t = 53t + -92

Reorder the terms:
-2 + 23t = -92 + 53t

Solving
-2 + 23t = -92 + 53t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-53t' to each side of the equation.
-2 + 23t + -53t = -92 + 53t + -53t

Combine like terms: 23t + -53t = -30t
-2 + -30t = -92 + 53t + -53t

Combine like terms: 53t + -53t = 0
-2 + -30t = -92 + 0
-2 + -30t = -92

Add '2' to each side of the equation.
-2 + 2 + -30t = -92 + 2

Combine like terms: -2 + 2 = 0
0 + -30t = -92 + 2
-30t = -92 + 2

Combine like terms: -92 + 2 = -90
-30t = -90

Divide each side by '-30'.
t = 3

Simplifying
t = 3

See similar equations:

| x-47=-39 | | 78n+100=550 | | 3(x-3)+21=3x+12 | | -5m+4m+2=5m+8 | | 5(x-8)+9=-60 | | 8=-2p-10 | | 4(-8h-8)=-3h+200 | | 6x+21=4x-57 | | 3-4(x-2)-4=-3x-3-6 | | 41=7x-8 | | 6d+10=12d-5 | | -7k-4k=-4k-k-12 | | x+17=3x-3 | | t+30=22 | | (x-3)(x-3)-12=0 | | 5-3n=-6n-13 | | -9-2f=5f-23 | | 7c+3(c-4)=8 | | 111=-12x+15 | | 30-15w=2w-6 | | 2x+2+7=16 | | -2x+4=ax+b | | 6x-5=7x-13 | | 1+2x=-7+x | | 4(2x+1)=8x+11 | | 6x-6+x-3=2x-1 | | 3(2x-5)=81 | | 5x+87=54 | | -7n+8=15 | | 2x-10=2x+20 | | z-16=-15 | | 5z-2=4z |

Equations solver categories